Under the whispering door ebook - Klune, TJ (2021)
A NEW YORK TIMES, USA TODAY, AND INDIE BESTSELLER One of Buzzfeed 's "Best Books of 2022"! An Indie Next Pick! A Locus Awards Top Ten Finalist for Fantasy Novel A Man Called Ove meets The Good Place in Under the Whispering Door , a delightful queer love story from TJ Klune, author of the New York Times and USA Today bestseller The House in the Cerulean Sea . Welcome to Charon's Crossing. The tea is hot, the scones are fresh, and the dead are just passing through. When a reaper comes to collect Wallace from his own funeral, Wallace begins to suspect he might be dead. And when Hugo, the owner of a peculiar tea shop, promises to help him cross over, Wallace decides he's definitely dead. But even in death he's not ready to abandon the life he barely lived, so when Wallace is given one week to cross over, he sets about living a lifetime in seven days. Hilarious, haunting, and kind, Under the Whispering Door is an uplifting story about a life spent at the office and a death spent building a home. At the Publisher's request, this title is being sold without Digital Rights Management Software (DRM) applied.